Parvalbumin and parvalbumin chandelier interneurons in autism and other psychiatric disorders - Juarez, Pablo; Martínez Cerdeño, Verónica (Frontiers in Psychiatry, 2022)
Parvalbumin (PV) is a calcium binding protein expressed by inhibitory fast-spiking interneurons in the cerebral cortex. By generating a fast stream of action potentials, PV+ interneurons provide a quick and stable inhibitory output to pyramidal neurons. Their fast kinetics, while advantageous for regulating cortical signaling, also leave them vulnerable to metabolic stress, both during development and during maturity. Chandelier (Ch) cells are a type of PV+ interneuron that modulate the output of pyramidal neurons, synchronize spikes within neuron populations, and generate cortical gamma oscillations, by directly innervating the pyramidal axon initial segment. Changes in the morphology and/or function of PV+ interneurons, mostly of Ch cells, are linked to neurological disorders. In autism, the number of PV+ Ch cells is decreased across several cortical areas suggesting a weaker synaptic strength. A reduction of PV+ Ch cell number has also been linked to schizophrenia, epilepsy, and bipolar disorder. Herein, we review existing evidence about the role of PV and PV+ Ch cells in autism and other psychiatric disorders.